1985
DOI: 10.3109/01485018508986904
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors in Stromal and Epithelial Fractions of the Ventral Prostate of Rats

Abstract: The cytosol from rat ventral prostates contains two estrogen-binding components that can be separated in a glycerol gradient: a highaffinity (KD = 4.2 X lo-'' M), low-capacity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Scatchard analysis revealed that the hormone appeared to exert effects on one of the two binding components which can be demonstrated in the cytosol, the relatively lower-affinity high-capacity component which appears to be distinct from the classical oestrogen receptor (Purvis et al, 1985). Because the analysis was carried out on pools of tissue it was not possible in this study to obtain statistical proof for the apparent effect on the low affinity component.…”
Section: Discussionmentioning
confidence: 93%
“…Scatchard analysis revealed that the hormone appeared to exert effects on one of the two binding components which can be demonstrated in the cytosol, the relatively lower-affinity high-capacity component which appears to be distinct from the classical oestrogen receptor (Purvis et al, 1985). Because the analysis was carried out on pools of tissue it was not possible in this study to obtain statistical proof for the apparent effect on the low affinity component.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, a wide variety of hormones and drugs have been shown to induce ODC in other tissues (Russell -1980), and it is unlikely that androgens constitute the only stimulus to its activation. Prostatic epithelium is equipped with other classes of receptors including those for oestrogen (Purvis et al -1985) and prolactin (Charreau et d. -1977) and the latter hormones have been shown to interact with ODC in other organs (Richards -1975;Rorke et al -1984).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen and progestin receptors have also been detected in both epithelium and stroma (173,189). Estrogen receptors appear to be elevated in the stroma (180, 186,187,193,194). Thus, there is now general agreement that stromal cells are clearly important hormone targets which are metabolically active and thus may play a fundamental role in hormonal response.…”
Section: Regulation Of Prostatic Growthmentioning
confidence: 96%